Zastosowanie syntetycznego analcymu do usuwania metali ciężkich z roztworów wodnych = Applications of synthetic analcime for reduction of heavy metals in water solutions - Makosz, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the possibility of sorption of heavy metals ? Pb and Ni on synthetic analcime, obtained on the basis of fly ash. The analcime was synthesized by hydrothermal method with alkaline activation.
Keywords: analcym; NaP1; metale ciężkie; sorpcja; roztwory wodne; analcime; heavy metals; sorption; water solutions